If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 = 6 + -5r Solving 26 = 6 + -5r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '5r' to each side of the equation. 26 + 5r = 6 + -5r + 5r Combine like terms: -5r + 5r = 0 26 + 5r = 6 + 0 26 + 5r = 6 Add '-26' to each side of the equation. 26 + -26 + 5r = 6 + -26 Combine like terms: 26 + -26 = 0 0 + 5r = 6 + -26 5r = 6 + -26 Combine like terms: 6 + -26 = -20 5r = -20 Divide each side by '5'. r = -4 Simplifying r = -4
| 25+5y=35-3y | | 25+0.21y=35+0.13x | | (4w-28)+(1w+13)=180 | | 4+2q=-4 | | (-5+-3m)(3+-5m)=0 | | y=5sin(5x) | | 7x+4-2x-7=-23 | | 27x^3+27x^2+9x+1= | | 16x^2+18=-609 | | 15000-500x+4x^2=0 | | 1=5-v | | (8+4i)-(9-3i)= | | x=10-6y | | (x,4),(6,-1)= | | 6x=4x-6 | | 15000-500x+4x^2=10400 | | 6g+4=58 | | -5x^2-38x-21=0 | | 2(q-4)=6 | | 3x=3*2+x*2 | | 4y+3=-3+2y+14 | | 2.25=qt | | 1-3x=2(-4x+7) | | 4a+2b=5 | | -10=-4+2k | | -5(x-4)-9=11 | | 14=8+2p | | 7(2x+5)=4x | | 10b^2-11b+3=0 | | 16=3s-4 | | 5+7i^2= | | (5x^2-7x-2)+(9x^2+8x-4)= |